CERA-TVR: A framework for interactive high-quality teravoxel volume visualization on standard PCs - Engel, K. (2011 IEEE Symposium on Large Data Analysis and Visualization, 2011)
We present a volume visualization framework that allows high-quality interactive rendering of teravoxel scale volume data sets on standard PCs. It is based on a progressive multi-resolution out-of-core volume rendering approach. Data loading is controlled by rays that are cast through the volume data set. The tree structure representing the multi-resolution hierarchy is traversed and updated directly by the GPU during ray casting. Consequently, occluded and empty data is never loaded or rendered. The framework is able to render dense, anisotropic, scalar volume data on regular grids with all common rendering modes.